Lucid dreaming - Gackenbach, Jayne; LaBerge, Stephen (My University, 2000)
In this revised and thoroughly updated edition of their classic text, the editors have invited experts to provide definitive reviews and analyses of a wide range of anomalous experiences, from commonly documented sensations and perceptions like synesthesia, lucid dreaming, out-of-body experiences, and auditory and visual hallucinations, to rarer and more seemingly inexplicable experiences such as anomalous healing, past-lives, near-death, mystical experiences, and even alien abductions ... The book makes a compelling case for the inclusion of these marginalized and under-recognized experiences as not merely incidental, but essential to our understanding of human psychology.
Keywords: Consciousness